Strategi Guru Menggunakan Teori Belajar Sosial untuk Meningkatkan Disiplin dan Motivasi Belajar - Alisia Zahro’atul Baroroh; Ani Ani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study is grounded in the issue of low student discipline and learning motivation in elementary schools, which requires teachers to apply more effective and context-based instructional strategies. The purpose of this research is to describe how teachers utilize social learning theory to enhance students’ discipline and motivation, as well as to analyze the impact of these strategies on classroom behavior and student engagement. This research employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation involving teachers and students. The findings show that teacher strategies integrating modeling, positive reinforcement, and collaborative learning successfully create a more conducive learning environment. The use of teacher and peer role models was found to increase compliance with classroom rules, while the provision of positive feedback encouraged students to participate more enthusiastically in learning activities. Moreover, socially interactive learning helped students develop confidence and active engagement. The implications of this study affirm that social learning theory can serve as a strong foundation for teachers to design strategies that promote positive behavior and intrinsic motivation, making it highly relevant for integration into daily classroom practice.